Caracterização da expressão de genes de peptídeos antimicrobianos (PAM’s) da lagarta Spodoptera frugiperda (Lepidoptera: Noctuidae) em resposta ao desafio microbiano - Feistler, Elisiane Pinto (2020)
Insects represent the most numerous class of living organisms. Faced with infections, they have multiple innate defense reactions. They have a wide variety of species being adapted to different habitats, and because of this, it is of great scientific importance, the study of their innate immune system in the face of aggressions, whether environmental or biological through pathogenic microorganisms. The Spodoptera frugiperda caterpillar (Lepidoptera: Noctuidae) insect model and object of this study, is considered a pest for corn, rice, cotton, among others, and has an immune system that is capable of protecting it from several challenges. The innate humoral immunity in the Insecta class includes the expression of Antimicrobial Peptides (AMP’s) produced in the organ analogous to the liver of vertebrates, called the fatty body. AMP’s are produced and secreted in the hemolymph, and this production can be induced, increasing expression in the face of exposure to pathogens. AMP’s basically act by disintegrating the bacterial cell wall, causing cell lysis and death. This makes them strong candidates to be used as new antimicrobials against mainly bacterial infections, since there is currently a wide range of multi-resistant microorganisms. This study aimed to characterize the expression of Atacin and Gloverin, both AMP’s already described in other species of Lepidoptera; however not yet reported in S. frugiperda. The detection of peptides in the larval phase of S. frugiperda was performed by Polymerase Chain Reaction (PCR) with primers designed from homologous sequences of these peptides from of order Lepidoptera. The experiments were conducted through extraction of total RNA from the fatty body, synthesis of cDNA and conventional RT-PCR, after the challenge of the worms with microorganisms. The results show that the challenge of the worms with the microorganisms (Escherechia coli, Bacilus subitlis and Beuaveria bassiana) caused an increase in the expression of the AMP’s genes by RT-PCR. In addition, the gene expression was observed in the hemolymph of the worms through the extraction of proteins and visualization in Tricina SDS-PAGE, where it was verified the presence of the AMP’s induced with molecular mass below 6.5 kDa. The peptide bands with molecular mass of 6.1 kDa and 4.7 kDa, respectively, were removed and trypsinized from the 1-D gel and subjected to Mass Spectrometry (Maldi-Tof), however, no positive identification was obtained with the Maldi-Tof mass spectrometry data. However, the induction of peptide bands with the microbial challenge suggests that these are probable peptides of the class of AMP’s with immune function in S. frugiperda.